Policy Learning and Handling of Covid-19 in Indonesia - Leo Agustino (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2021)
Abstract This article discusses the policy learning process in managing the Coronavirus Disease 2019 (COVID-19) within Indonesia and asks several questions regarding the policies formulated and implemented, as well as how the government "learns" and handles the pandemic. Furthermore, this study used a qualitative research method supported by literature discourse methods and online interviews, as well as a policy learning theory-based analysis. According to the results, the Indonesian government has learned a lot from other countries, however, the country has been rather slow in anticipating the pandemic, causing a minimal sense of crisis and urgency. In addition, the low level of trust and seriousness in the government has implications for a less harmonious relationship between the center and the regions. Also, the inter-institutional coordination and the inaccuracy of actors in handling the pandemic is an unresolved problem, therefore, the distribution location expands continually and the infection curve never slopes. Keywords: Policy Learning; Handling; COVID-19; Policy